Kesiapan SKPD pada Implementasi Perda Anti Trafficking Kota Parepare No. 6 Tahun 2011 - Rahmah Bakoko; Hamdanah Hamdanah; Nurhamdah Nurhamdah (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2019)
This research analyzed the implementation of Human Trafficking Policy (Peraturan Daerah No.6, 2011) in Parepare, South Sulawesi Indonesia. There have been several human trafficking cases across the province and the motives were varied. The common trafficking cases were initially offered as labor migration to Malaysia. The victims were often young girls who came from low social economic status. In Depth Interview and Focus Group Discussion were conducted to find out the readiness of the related stake holders in implementing the Human Trafficking Policy in Parepare. The local government of Parepare (SKPD) is aware of the Human Trafficking Policy and they have been working closely with the labor department, local universities, schools, Non-Governmental Organizations (NGOs) to advocate and to educate the local communities, especially girls to prevent more human trafficking in Parepare, South Sulawesi.